Suicide Attempt Survivorship and Designation as a Concealable Stigmatized Identity. Issue 3 (July 2018) - Fulginiti, Anthony; Frey, Laura M.
Despite literature on unique challenges faced by people living with concealable stigmatized identities (CSIs), no research has explored this concept among suicide attempt survivors. Social network interviews with 26 attempt survivors about their family relationships were used to assess whether attempt-survivor status is consistent with CSI criteria. Participants concealed their attempt from 51% of family members and perceived that 46% of them held stigmatizing attitudes toward attempt survivors. Additionally, 42% agreed that being a survivor is central to who they are, and 46% indicated they commonly thought about being an attempt survivor. Applying the CSI concept to attempt survivors establishes conceptual linkages to resources and interventions developed for other CSIs, which could increase the field's ability to respond to attempt-survivor needs.